2018
DOI: 10.1111/jac.12261
|View full text |Cite
|
Sign up to set email alerts
|

Exogenous application of allelopathic water extracts helps improving tolerance against terminal heat and drought stresses in bread wheat (Triticum aestivum L. Em. Thell.)

Abstract: The allelopathic water extracts (AWEs) may help improve the tolerance of crop plants against abiotic stresses owing to the presence of the secondary metabolites (i.e., allelochemicals). We conducted four independent experiments to evaluate the influence of exogenous application of AWEs (applied through seed priming or foliage spray) in improving the terminal heat and drought tolerance in bread wheat. In all the experiments, two wheat cultivars, viz. Mairaj‐2008 (drought and heat tolerant) and Faisalabad‐2008 (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
12
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(15 citation statements)
references
References 62 publications
1
12
0
Order By: Relevance
“…The current study revealed that MLE application significantly improved gas exchange attributes, physiological responses, enzymatic activities and productivity of rice crop under drought stress. The findings relating to gas exchange attributes are in agreement with previous studies reporting that drought stress significantly reduced A, gs and E [28,29]. The A and other activities in flag leaf are the major source of crop productivity; however, these are susceptible to abiotic stresses, including drought stress [30].…”
Section: Discussionsupporting
confidence: 91%
“…The current study revealed that MLE application significantly improved gas exchange attributes, physiological responses, enzymatic activities and productivity of rice crop under drought stress. The findings relating to gas exchange attributes are in agreement with previous studies reporting that drought stress significantly reduced A, gs and E [28,29]. The A and other activities in flag leaf are the major source of crop productivity; however, these are susceptible to abiotic stresses, including drought stress [30].…”
Section: Discussionsupporting
confidence: 91%
“…Seed priming with allelopathic water extract significantly improves the seed emergence, plant growth, and yield of various field gown crops, especially under environmental cues [ 33 , 34 , 35 ]. Under heat and drought stress, seed priming with allelopathic water extract improves the stay green, proline, and phenolic content, and stabilizes the biological membrane, thereby enhancing the plants’ tolerance to abiotic stresses [ 33 ]. Under salinity stress, seed priming with 5% aqueous sunflower extract can enhance the tolerance in rice cultivars [ 36 ].…”
Section: Introductionmentioning
confidence: 99%
“…Various allelochemicals have been identified in several plants, which can improve crop performance under normal and stress conditions. The exogenous application of allelopathic extracts may contribute to the production of endogenous secondary metabolites, which helps crops to perform better even under environmental cues [ 33 ]. The improved crop performance under exogenous application of allelopathic aqueous extract may be due to the increased accumulation of compatible solutes.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Adaptive strategies that are induced during the drought process help plants survive (Nguyen et al 2016). Plants such as maize (Zea mays L.) reduce tissue dehydration, either via tolerance to lower tissue water potential or by maintaining the water potential (Wu and Cosgrove 2000;Farooq et al 2017Farooq et al , 2018. To successfully minimize water loss, plants limit transpiration by decreasing leaf area, closing their stomata and accelerating leaf senescence, resulting in improved water-use efficiency (WUE) (Franks et al 2015;Farooq et al 2019) or reduced photosynthesis (Shi et al 2016).…”
Section: Introductionmentioning
confidence: 99%